PROTECT BALI: THE EVOLUTION OF REGULATIONS IN ADDRESSING CHALLENGE TO OVERTOURISM IN BALI - Trisno, Alexandra Kyra (Jurnal Pacta Sunt Servanda, 2024)
Bali Island is a premier tourist destination known for its natural beauty and rich cultural heritage. However, uncontrolled tourism growth or overtourism has triggered significant environmental, social, and cultural challenges. This research aims to evaluate the effectiveness of existing regulations and examine the urgency of establishing new ones to address the growing complexity of tourism impacts. This study employs a normative legal method using a conceptual approach, comparative analysis, and legislative review. The findings indicate that although national and regional laws, such as Law No. 10 of 2009 and Bali Regional Regulation No. 5 of 2020, promote sustainable tourism, their implementation faces challenges, including weak enforcement and limited community participation. Thus, new, more adaptive regulations are needed that integrate environmental, social, and cultural principles. These measures are essential to safeguard Bali’s identity and ensure the sustainability of its tourism industry amidst globalization and increasing visitor pressure.